Análisis de la fotografía en el cine producido en Ecuador. Sin muertos no hay carnaval - Madrid Ochoa, Mercedes Lisset (2019)
In the analysis of "Without the Dead, there is no Carnival", topics were discussed about the reality of Ecuadorian society, as well as about poverty and the problems that are found in the country and Ecuadorian society in general. The people who worked with Sebastián Cordero in his first film productions continued to dabble and participate in later films of national character. Arturo Yépez Z. producer of the film, gave very good information about the Latin themes, those that use Cordero and about the importance of film festivals for this subject of study. Another subject of the subjects is a subject where the Latin American cinema is presented, whose goal is to produce cinematographic productions, like the European one and the social subjects that are given in the Latin cinema.